PENGARUH PEMBERIAN PENGHARGAAN DAN PELATIHAN KERJA TERHADAP PRODUKTIVITAS KERJA PADA PT. BANK RAKYAT INDONESIA (PERSERO) CABANG TELUK BETUNG KOTA BANDAR LAMPUNG - ridwan rangkuti (Universitas Bandar Lampung (UBL), 2017)
The problem in this research is how the employSee's productivity PT Bank Rakyat Indonesia (Persero) is influenced by rewards and job training. This study aims to determine, analyze, and explain the influence of rewards and job training to employee productivity. The hypothesis formulated is awarding and work facilities effect on employee productivity, either partially or simultaneously. The population used in this study amounted to 51 employees. Data collection techniques by observation, documentation and questionnaires. Analysis of data using a quantitative approach. If the primary data using SPSS statistical tools for calculation of linear regression model. Results of testing the hypothesis by partial indicate that the award effect on employee productivity and contribute to employee productivity, job training effect on employee productivity and contribute to employee productivity, hypothesis testing showed that the rewards and job training together positive effect on employee productivity. Keywords: awards, job training, work productivity.